Development of a Jigsaw Type Cooperative Learning Model Based on 6C to Improve Social Attitudes and Interpersonal Skills Students' Civics in Primary Schools - Pasaribu, Eva; Sitohang, Sukardo; Simanjuntak, Sondang (International Journal of Contemporary Studies in Education, 2024)
This research aims to: (1) produce a Jigsaw Type Cooperative Learning Model product, (2) determine the level of feasibility of the Jigsaw Type Cooperative Learning Model product in thematic subjects, and (3) determine the effectiveness of using the Jigsaw Type Cooperative Learning Model product. This development research refers to the steps developed. Type of research The development procedure includes stages. The development model applied by researchers is the ADDIE model. The ADDIE development model consists of five stages, namely Analysis, Design, Development, Implementation and Evaluation. Research results: Field trial subjects consisted of 30 class V students at SD Negeri 096140 Parhundalian. Data collection uses assessment sheets, questionnaires and responses. The data analysis technique uses a Likert scale. The results of the research show that the Jigsaw Type Cooperative Learning Model for class V elementary school according to material experts, model experts is in the very feasible category. The implementation and use of the Jigsaw Type Cooperative Learning Model can generally be carried out in the very feasible category and has received a positive response from students